Br-319 Highway, Brazil: Geopolitics, Transportation, and Pioneer Fronts - Oliveira-Neto, Thiago; Batista Nogueira, Ricardo José (Revista Geográfica de América Central., 2024)
This paper aims to provide an overview of the BR-319 highway (connecting Manaus and Porto Velho, Brazil) through a geopolitical analysis of transportation and pioneer fronts. The objective is to highlight the State’s role in the Amazon and the process of Brazilian territorial integration. It also points out considerations on cargo and passenger transport activities organized along this corridor and highlights the existence of pioneer fronts with various temporalities. Bibliographic and historical surveys were conducted, involving the examination of newspapers from the decades 1960 to 2000. Additionally, fieldwork was undertaken between 2014 and 2022. Following the completion of the fieldwork, the study identified the organization of transport activities and the development of pioneer fronts in the southern segment of the highway in the district of Realidade, within the municipality of Humaitá-AM.